PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MOTIVASI BERWIRAUSAHA MAHASISWA JURUSAN PENDIDIKAN EKONOMI UNIVERSITAS NEGERI PADANG - Rosyanti Rosyanti; Agus Irianto (Jurnal Ecogen, 2019)
Abstract: The research aims to identify and analysis the effect of entrepreneurship education and family environment on entrepreneurial motivation of students of economics education majoring in Padang State University. The population in the research were students 2015 and 2016 economic education majoring in Padang State University. The analytical method used is multiple regression analysis using the SPSS version 21 program. The result show that 1) entrepreneurship education have a not significant effect on entrepreneurial motivation of students of economics education majoring in Padang State University 2) The family environment have a significant effect on entrepreneurial motivation of students of economics education majoring in Padang StateUniverity Keywords: entrepreneurship education, family environment, entrepreneurial motivation